Vesicular adenomyomatosis - Delgado, Bolívar; Zagias, Miguel; Chiozzone, Martha (Cirugía del Uruguay, 1972)
The authors revise the subject, and stress its anatamopathologic, radiological and therapeutic aspects. In their opinion this disease is a mioglanduliform displasia, fundamentally localized, and thus disagree with the broad criteria sustained by authors such as Jutras and Aguirre. The paper gives a detailed account of the radiological alterations which characterize this disease. When the patie.nt presents the typical biliary suffering, even in the absence )f associated litiasis, they propase a cholecystectomy. This therapy has shown very good results in the patients operated.